Is jump ability related to specific short sprints in young female volleyball players? - Busca, B.; Pena, J.; Moreno, D.; Morales, J. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Volleyball players sprint in two game-situations: block and court-defence. To react as quick as possible and complete the balanced displacement required for a satisfactory ball contact is necessary to perform specific techniques. Is widely known that jumping ability and muscular leg power are related to sprint ability (Sheppard et al, 2008; Rigs & Sheppard, 2009). The objective of the study is to examine the relationship between jump ability and specific short-sprint velocity using specific movement patterns. Methods: A group of 14 female young volleyball players (age = 18.2 ± 0.8, height: 178.3 ± 3.1 cm, weight: 63.2 ± 7.2 kg), members of a training group based at the National Training Center of Barcelona, participated in this study. Time of short-sprint were assessed using two photocell gates Velleman PME10D® connected to a Chronopic of Chronojump®. Jumps were measured with the same system but using a jump mat. The measurement protocol was performed in the following order: SJ, CMJ, ABK, VJ (volleyball jump), DEF (defensive short sprint) and BLOCK (block short displacement). A correlation analysis was performed to evaluate the association between the variables. Results: We observed a significant correlation between all jump protocols (r > 0.89; p< 0.01). We found significant relationship between BLOCK and SJ (r = -0.79; p< 0.01), CMJ (r = -0.78; p< 0.01), ABK (r = -0.79; p< 0.01) and VJ (r = -0.80; p< 0.01). But only a significant relationship between DEF and ABK (r = -0.51; p< 0.05). Both short sprint protocols were also related (r = 0.68; p< 0.01). Discussion: These findings suggested the importance of the vertical jump skills for the acceleration phase, brake phase and the abrupt change of direction actions in sprint ability. So, this ability requires a high validity of the assessment method. From our point of view and knowledge, the only specific test in volleyball, the 5-meter agility test used by Barnes et al (2007), was conducted without this specificity because no instructions about how the subjects had to move were done. Moreover, the distances proposed were too long and redundant. The higher relationship observed in our study could be explained by the higher specificity of our test.